1965
DOI: 10.1192/bjp.111.479.919
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Bristol

Abstract: “That the deceased took his life while the balance of his mind was temporarily disturbed” has been the Coroner's traditional verdict in cases of suicide; a verdict adopted to circumvent retribution by society and particularly to allow of burial in consecrated ground and avoid forfeiture of property to the Crown (Williams, 1958). There is a distinction between such a finding with its legal import and that of the psychiatric assessment, and this must necessarily affect psychiatric studies undertaken in the endea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…The correlation of unemployment and suicide has been suggested by Sainsbury (1955), Seager and Flood (1965) and Robin et al (1967). In our study, it is found that the suicide ratio of economically inactive to active elderly is about six to one.…”
Section: Discussionmentioning
confidence: 56%
“…The correlation of unemployment and suicide has been suggested by Sainsbury (1955), Seager and Flood (1965) and Robin et al (1967). In our study, it is found that the suicide ratio of economically inactive to active elderly is about six to one.…”
Section: Discussionmentioning
confidence: 56%
“…Studies of suicide (being heavily contributed to by major depressive disorders), support these findings [2], Studies of the seasonal incidence of affective disorders have demonstrated a tendency for spring and fall peaks of depression and a summer peak of mania [1]. A sex differential has also been observed.…”
supporting
confidence: 61%
“…This finding is similar to several other studies and suggests that attempted suicide is a problem of young adults. [16][17][18] There were predominantly more males (54%) than females (46%) in our study. This is similar to many Indian studies that have reported a preponderance of males as compared to females.…”
Section: Discussionmentioning
confidence: 99%